Prevalence and predictors of khat chewing among Ethiopian university students: A systematic review and meta-analysis. - Alemu Gebrie (PLoS ONE, 2018)
Khat chewing has become a common practice among university students in developing countries like Ethiopia. It has a potential effect on physical, mental, social and cognitive aspects of student functioning. In Ethiopia, study findings regarding the prevalence of khat chewing were highly dispersed and inconsistent. Therefore, this systematic review and meta-analysis estimates the pooled prevalence of khat chewing and its predictors among Ethiopian university students.A systematic review and meta-analysis was conducted to assess the prevalence and predictors of khat chewing among university students in Ethiopia. We searched literature from the databases of PubMed, Google Scholar, Science Direct, and the Cochrane Library. A total of 24 Ethiopian studies reporting the prevalence of khat chewing among university students were included. Data were extracted using a standardized data extraction format prepared in Microsoft Excel and the analysis was done using STATA 14 statistical software. To assess heterogeneity, the Cochrane Q test statistics and I2 test were used. Since the included studies exhibit high heterogeneity, a random effect meta-analysis model was computed to estimate the pooled prevalence of khat chewing. Moreover, the association between predictor variables, and khat chewing practice were examined.The meta-analysis of 24 studies revealed that the pooled prevalence of khat chewing among university students in Ethiopia was 23.22% (95% CI: 19.5, 27.0). In the subgroup analysis, the highest prevalence was observed in Oromia region (31.6%; 95CI: 21.2, 41.9) whereas the lowest prevalence was observed in Amhara region (18.1%; 95%CI: 12.4, 23.8). Being male OR: 2.76 (95% CI 1.64, 4.63), family khat chewing practice OR: 2.91 (95% CI 1.06, 7.98), friend khat chewing habit OR: 4.74 (95% CI 3.48, 13.06), alcohol drinking OR: 7.06 (95% CI 5.65, 8.82) and cigarette smoking habit OR: 15.11 (95% CI 8.96, 25.51) were found to be predictors of khat chewing.The study found that the prevalence of khat chewing among university students was quite common, with slightly more than 1 in 5 students engaging in the use of this substance. Being male, family khat chewing practice, friend's khat chewing habit, alcohol drinking, and cigarette smoking were found to be predictors of khat chewing practice among university students.